2023
DOI: 10.1136/archdischild-2023-325605
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in children with congenital heart disease: a comparative study with health counterparts

Abstract: ObjectiveResilience is a complex, yet rather unexplored topic in patients with congenital heart disease (CHD). The goal of this study was to assess and compare resilience in children with CHD with healthy controls during the COVID-19 pandemic.Design and patientsFrom June 2020 to June 2021, 124 children with various CHDs (14.6±2.1 years, 49 girls) and 124 matched healthy controls (14.8±2.0 years, 49 girls) completed the Resilience Scale-11 short version.ResultsResilience was significantly reduced in children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…These results contradict published findings. Köble and colleagues have shown that adolescents with cCHD score significantly lower than controls in a self-reported resilience questionnaire . This study used the 11-item version (RS-11) of the same questionnaire that was used in our study (RS-13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results contradict published findings. Köble and colleagues have shown that adolescents with cCHD score significantly lower than controls in a self-reported resilience questionnaire . This study used the 11-item version (RS-11) of the same questionnaire that was used in our study (RS-13).…”
Section: Discussionmentioning
confidence: 99%
“…Köble and colleagues have shown that adolescents with cCHD score significantly lower than controls in a self-reported resilience questionnaire. 25 This study used the 11-item version (RS-11) of the same questionnaire that was used in our study (RS-13). Another study found higher resilience in adolescents with cCHD relative to controls assessed with the Connor-Davison Resilience Scale, which assesses similar personality traits as the RS-13.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation